Analysis of Flow over a Circular Cylinder Fitted with Helical Strakes. (2016) - Ranjith, E.R.; Sunil, A.S.; Pauly, Lippin
Abstract: The effectiveness of the helical strakes in suppressing the vortex-induced vibration (VIV) of a rigid cylinder is investigated by providing a three start helical strakes around a circular cylinder at two Reynolds numbers (100&28000). While the effect of helical strakes on suppression of vortex shedding has been studied extensively, the mechanism of VIV mitigation using helical strakes is much less well documented in the literature. In the present study, a rigid circular cylinder of diameter d=40 mm attached with three-strand helical strakes of dimensions of 10d in pitch and 0.15d in height was tested by simulation. To numerically simulate vortex shedding, CFD is used to calculate the unsteady flow that arises from a fluid moving past an obstruction. A computational grid independence study has been done for flow over the circular cylinder and the grid resolution in which there is faster recovery of coefficient of lift is taken for the simulation. The contours of static pressure, velocity magnitude and vorticity magnitude and the hydrodynamic coefficients Cd and CL are obtained. It is found that, as expected, the straked cylinder has a higher drag coefficient in comparison with a smooth bare cylinder. The helical strakes can reduce VIV by about 99%.